Rehabilitation after ankle fracture treatment (RAAFT): facilitating safe weight-bearing after ankle fracture surgery - Bretherton, C (2022)
For as long as orthopaedic surgeons have treated patients with ankle fractures, surgical dogma has enforced weight bearing restrictions on patients postoperatively.